Simulasi Hidrodinamika pada Tikungan Sungai Wonokromo Surabaya Menggunakan Delft3D - Akhmad Fauzi Almudhoqi; Andi Patriadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the existing hydrodynamic conditions at the bend of the Wonokromo River using the Delft3D numerical model. The simulation was conducted over 24 hours using topographic, bathymetric, tidal, and flow data with a 10-year return period. The simulation results showed a maximum tide of 1.526 m and a minimum tide of -1.078 m relative to Mean Sea Level (MSL). The maximum flow velocity at the observation point reached 1.104 m/s, while the minimum velocity was 0.607 m/s. Model validation results yielded a Nash-Sutcliffe Efficiency (NSE) value of 0.853 and an RSR of 0.384, which fall into the